Digital-Based Management of Incoming and Outgoing Mail Archiving at Educational Institution - Luthfia Labibah; Qomaruddin Qomaruddin; Nur Fatih Ahmad; Ririn Inayatul Mahfudloh (Mudir: Jurnal Manajemen Pendidikan, 2025)
The management of incoming and outgoing mail archives is essential in madrasah administration. The manual system that is still commonly used often faces obstacles such as difficulty in retrieving documents, the risk of loss, and inefficient storage. Archive digitalization becomes a solution to improve the effectiveness of archive management. This study aims to analyze digital archive management and identify the benefits and challenges of its implementation in madrasahs. The method used is qualitative, involving interviews, observations, and document analysis. The results show that the digital system can accelerate document retrieval, reduce the risk of loss, and improve the quality of administration. However, challenges remain, such as limited human resource competence and resistance to change. This study contributes to the development of a more effective digital archive management model for madrasahs.